1996
DOI: 10.1046/j.1365-2842.1996.d01-186.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the articulation after glossectomy

Abstract: Rehabilitation of the oral cancer patient should aim to achieve not only morphological restoration but also post-operative functions. However, there are few reports describing quantitative evaluation of the latter. The authors have attempted quantitative evaluation of post-operative articulatory function after glossectomy, and report the evaluation of it by speech intelligibility, electropalatography (EPG), and acoustical analysis. Subjects were five directly sutured patients and five patients reconstructed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 0 publications
1
31
0
Order By: Relevance
“…In this study, tongue pressure was examined by using a balloon-type measurement device in patients after tongue tumor resection and reconstruction. Few studies have measured tongue pressure after tumor resection and reconstruction [7,8]. Others have reported that disease severity and tongue resection type strongly affect postoperative speech and swallowing ability [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, tongue pressure was examined by using a balloon-type measurement device in patients after tongue tumor resection and reconstruction. Few studies have measured tongue pressure after tumor resection and reconstruction [7,8]. Others have reported that disease severity and tongue resection type strongly affect postoperative speech and swallowing ability [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is true that the tendency is for patients with primary closure to have lessened tongue resection. Another study indicated that the patients receiving flap reconstruction displayed higher oral function than those patients with primary closure alone [7]. Thus, through advances of surgical flap reconstruction, outcomes of tongue flap reconstruction appear to have improved substantially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Wakumoto et al 4 have attempted quantitative evaluation of postoperative articulatory function after glossectomy, by speech intelligibility, electropalatography (EPG), and acoustic analysis. Several methods are utilized to evaluate oronasal separation and articulation.…”
Section: Evaluation Of Speech Functionmentioning
confidence: 99%
“…The effects of oral cancer surgery on speech have primarily been examined using subjective perceptual evaluation and transcription of tape-recorded speech samples (e.g. Wakumoto, Ohno, Imai, Yamashita, Akizuki, and Michi, 1996;Korpijaakko-Huuhka, Söderholm, and Lehtihalmes, 1999;Furia, Kowalski, Latorre, Angelis, Martins, Barros, and Ribeiro, 2001;Terai and Shimahara, 2004) and more objective methods of oral physiology including articulatory imaging (e.g. Georgian, Logemann, and Fischer, 1982;Schliephake, Schmelzeisen, Schönweiler, Schneller, and Altenbernd, 1998;Kimata, Sakuraba, Hishinuma, Ebihara, Hayashi, Asakage, Nakatsuka, and Harii, 2003;Sun, Weng, Li, Wang, and Zhang, 2007).…”
Section: Introductionmentioning
confidence: 99%